STUDY OF THE ACCENTUATED NEEDS OF YOUTH SATISFIED IN THE MEDIUM OF VIRTUAL SOCIAL NETWORKS - V. Voronin; M. Iontseva; M. Kerre (Вестник университета)
In the article are theoretically substantiated and empirically confirmed the accentuated needs of modern youth realized within the virtual environment of social networks: the need for success, the need to increase and maintain self-esteem, the need to have identification, the need to increase or maintain the status. The authors describe the two-stage research conducted in the social network, conducted within the framework of the dissertation of Bezbogova M. S. (currently Kerre M. S.) «Social networks as a factor in the formation of social attitudes of modern youth».